The Sense of Responsibility for own Health and the Influence of the Disease on Daily Functioning Among Patients with Multiple Sclerosis - Beata Gąsowska; Monika Chorąży; Katarzyna Krystyna Snarska; Cecylia Dolińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. MS is characterized by a large variety of symptoms, which negatively affects the functioning and quality of life of patients. Aim. The purpose of the work is determination of the impact of Multiple Sclerosis on the daily functioning of patients and assessment of the sense of responsibility for one’s own health among patients with Multiple Sclerosis. Material and Methods. The study included 97 patients suffering from Multiple Sclerosis, treated at the Department of Neurology, University Hospital in Białystok. Study group consisted of 73 women and 24 men. The research has been conducted using the diagnostic survey method with following research tools: Activities of Daily Living scale; Instrumental Activities of Daily Living scale; Multidimensional Health Locus of Control and a self-constructed questionnaire. Results. The average age of the respondents was 52 (±10.36) and was comparable for women and men — 52.33 (±10.97) years and 51.79 (±8.42) years, respectively. The duration of the disease was on average 8 years (±3.87). Among the respondents, from the beginning of the disease, on average 5.02 exacerbations of MS (±3.08) have been observed. The most significant problem for MS patients was sphincter control (45.36%), independent bath (34.02%) and use of the toilet (31.96%). According to Lawton’s scale, patients with MS had most difficulties going out for shopping and getting outside walking distance. With the duration of the disease, the internal location of health control decreased significantly. Conclusions. As a result of increasing restrictions on the independent functioning of patients with Multiple Sclerosis, the sense of control over their own health is located in external factors such as chance and the influence of others. (JNNN 2019;8(3):102–111)